Optimization of adsorption isotherm types for desiccant air-conditioning applications - Sultan, Muhammad; Miyazaki, Takahiko; Koyama, Shigeru (Renewable Energy, 2018)
The present study investigates five kinds of adsorbents for desiccant air-conditioning (DAC) applications. Each adsorbent yield distinctive water vapor adsorption isotherm that can be categorized as type-I, type-II, type-III, type-V, and type-linear on the basis of the International Union of Pure and Applied Chemistry (IUPAC) classification. Ideal DAC cycle is evaluated for the air-conditioning (AC) applications, and steady-state moisture cycled (MCSS) is estimated by means of adsorption isobars. Results showed that the adsorbent enabling type-linear adsorption isotherm gives maximum MCSS for industrial AC processes of matches manufacturing/drying/storage, rubber dipped goods storage and photo studio drying room. However, adsorbent enabling type-V adsorption isotherm is found the optimum adsorbent for tobacco stemming/stripping/softening and optical lenses grinding. For industrial AC process of dipped surgical articles; adsorbents enabling type-II, type-linear, and type-I adsorption isotherms are found the optimum choice at low (<68 °C), medium (68°C-87 °C), and high (>87 °C) regeneration temperatures, respectively. •Ideal temperature and humidity zones for various air-conditioning applications.•Adsorption modeling of five adsorbents enabling distinctive adsorption isotherms.•Optimization is made for IUPAC types of water vapor adsorption isotherms.•Different types of adsorption isotherms require different regeneration temperature.